2022
DOI: 10.1093/neuonc/noac243
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic upregulation of Schlafen11 renders 
WNT- and SHH-activated medulloblastomas sensitive to cisplatin

Abstract: Background Intensive chemotherapeutic regimens with craniospinal irradiation have greatly improved survival in medulloblastoma patients. However, survival markedly differs among molecular subgroups and their biomarkers are unknown. Through unbiased screening, we found Schlafen family member 11 (SLFN11), which is known to improve response to DNA damaging agents in various cancers, to be one of the top prognostic markers in medulloblastomas. Hence, we explored the expression and functions of SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To examine the reciprocal effects of BRCA1/2 and SLFN11, we employed the SLFN11-expressing ovarian endometrioid adenocarcinoma TOV-112D and medulloblastoma DAOY cell lines in their SLFN11-knockout (SLFN11-KO) counterparts, which we recently shown to be hypersensitive to camptothecin (CPT) and cisplatin [32,33], Deleterious mutations in BRCA1 and BRCA2 are absent in either cell line according to the Cancer Cell Line Encyclopedia database (https://discover.nci.nih.gov/rsconnect/cellminercdb/) [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the reciprocal effects of BRCA1/2 and SLFN11, we employed the SLFN11-expressing ovarian endometrioid adenocarcinoma TOV-112D and medulloblastoma DAOY cell lines in their SLFN11-knockout (SLFN11-KO) counterparts, which we recently shown to be hypersensitive to camptothecin (CPT) and cisplatin [32,33], Deleterious mutations in BRCA1 and BRCA2 are absent in either cell line according to the Cancer Cell Line Encyclopedia database (https://discover.nci.nih.gov/rsconnect/cellminercdb/) [39].…”
Section: Resultsmentioning
confidence: 99%
“…S8096) were obtained from Selleckchem. Generation of SLFN11-deleted cells SLFN11-knockout (KO) cells in DAOY were previously published [32] and SLFN11-KO cells in TOV-112D were generated in another study [33]. Disruption of the SLFN11 gene using the CRISPR/Cas9 method was reported previously [9].…”
Section: Methodsmentioning
confidence: 99%
“…Several efforts have been channeled towards targeting the different drivers that promote the development and maintenance of treatment resistance in medulloblastoma. In this context, Nakata et al showed that epigenetic targeting via the histone deacetylase (HDAC) inhibitor RG2833 in WNT and SHH medulloblastoma results in hypomethylation of the Schlafen11 gene and overproduction of SLFN11, which makes tumor cells vulnerable to cisplatin treatment as confirmed in rodent models [ 104 ]. Similarly, epigenetic regulation of MYC through pharmacological and genetic inactivation of the upstream Ableson tyrosine kinase (ABL1/2) results in decreased C-MYC expression and tumor progression.…”
Section: Therapeutic Modalities To Overcome Resistancementioning
confidence: 99%
“…These mutations offer the opportunity to develop clinical trials focused on specific subtypes of SHH-medulloblastoma across the age spectrum and explore the role of drugs targeting the spliceosome, synthetic lethality, or immunotherapy. Finally, other emerging markers of response to DNA damaging agents in solid tumors such as Schlafen family member 11 (SLFN11) have been shown to be differentially expressed across medulloblastoma subgroups, being more frequent in WNT and a proportion of SHH tumors and confer increasing sensitivity to cisplatin and topoisomerase inhibition in vivo and in vitro [59]. This may have implications for treatment selection in adults with medulloblastoma, for whom adjuvant chemotherapy has shown a survival benefit but is associated with significant toxicity.…”
Section: Clinical Impact In Ependymal Tumors and Medulloblastomamentioning
confidence: 99%